Differences in gastroprotective and mutagenic actions between polar and apolar extracts of Ananas ananassoides - Silva, J. S. [UNESP]; Andreo, M. A. [UNESP]; Tubaldini, F. R. [UNESP]; Varanda, Eliana Aparecida [UNESP]; Rocha, L. R. M. [UNESP]; Brito, A. R. M. S.; Vilegas, Wagner [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (Mary Ann Liebert, Inc., 2008)
Several plants are used in folk medicine to treat gastrointestinal disorders. Ananas ananassoides (Baker) L. B. Smith (Family Bromeliaceae) is a medicinal plant commonly used in the central region of Brazil against gastric pain. We evaluated two extracts (methanol [MeOH] and dichloromethane [DCM]) obtained from the leaves of A. ananassoides for their ability to protect the gastric mucosa against injuries caused by necrotizing agents (0.3 M HCl/60% ethanol, absolute ethanol, non-steroidal anti-inflammatory drugs, and pylorus ligation) in mice and rats. The best results were obtained after pretreatment with the DCM extract, whereas the MeOH extract did not show any significant anti-ulcerogenic activity but presented mutagenic action. The mechanism of action of the DCM extract suggested the effective participation of endogenous sulfhydryl group in the gastroprotective action. The data, taken together with the absence of acute toxicity and mutagenicity, indicate the apolar extract, instead of the polar, extract of A. ananassoides as a safe and potential new anti-ulcerogenic drug.
Keywords: Ananas ananassoides; anti-ulcerogenic activity; Bromeliaceae; endogenous sulfhydryls; mutagenicity